ON THE FORMATION OF YOUTH'S SPIRITUAL IMAGE - Valikhonova Gulnora Komiljonovna; Khusanova Madina; Jumaboeva Robiya (American Journals Publishing, 2024)
In this article, the authors analyze the issues of spirituality, responsibility of youth, their responsibilities to the future of the nation, spiritual image, worldview, views put forward by the ancestors regarding education.
Keywords: Education, spirituality, nation, example, example, influence, ideology.